Perceived Economic Impact of COVID-19 on Dental Practitioners: A Bi-Country Survey - Tariq, Khaloud; Iqbal, Kanza; Bhutta, Hadeer; Hassan, Muhammad; Baloch, Faisal (European Journal of General Dentistry, 2022)
Objective COVID-19 resulted in dentistry being declared high-risk occupation due to the mode of the spread of the virus. This resulted in partial and complete closure of dental practices around the world, reducing revenue of practitioners. Hence, study aims to evaluate financial impact on dental practitioners in Pakistan and UAE.Materials and Methods A questionnaire-based cross-sectional study was conducted from July 2020 to January 2021. It involved questions relating to demographics and financial challenges faced, associated with change in standard operating procedures due to pandemic. The descriptive statistics were expressed as frequency and percentage. Statistical analysis was performed by Chi-square test or Fischer's exact test.Results In total, 427 respondents participated in the study. Approximately half (55.7%) of the respondents had their practices shut down, while 89.9% observed decrease in patient flow. The majority (82.2%) of respondents had to buy personal protective equipment (PPE), whereas 66.7% had to pay a high cost for that. Almost 87.3% of respondents reported having experienced financial constraints because of the pandemic related changes to the practice. Moreover, 27.8% reported staff being laid off, which were mostly due to monetary constrictions.Conclusion Dental professionals faced a considerable impact on their practice and financial situation due to pandemic. Policies must be made to support such professionals in times of emergency who are at higher risk of being most affected with respect to health and finances.
Keywords: COVID-19; dentistry; dental clinics; dental practice; economic evaluation